Play more, enjoy more, keep playing; rugby is a simple game. Issue 3 (June 2021) - Jones, Ben; Hope, Ed; Hammond, Andrew; Moran, Jason; Leeder, Thomas; Mills, John; Sandercock, Gavin
Drop out and attrition rates in youth sport are well-documented in the literature. Research has found that children overwhelmingly state that enjoyment, fun, and positive experiences are the primary reasons to participate in sport. Competitive Engineering (CE) is a structurally-based competitive climate process designed to create a more positive experience in youth sport. CE encompasses changes to league structures, equipment, pitch-size, and game rules. For example, rule changes that stipulate greater involvement (e.g., playing time) or action (e.g., increasing scoring opportunities) are designed to improve engagement. Despite this, few studies have examined whether CE-based rule changes influence factors known to influence drop out from sport. The aim of this study was to assess the impact of a rule change in youth rugby whereby any player selected as part of a match day squad must play at least half a game or equivalent (i.e., the 'Half-Game Rule'). To achieve this, we studied the influence of the rule change on player reported outcomes throughout the 2017/2018 playing season. Players who "always or almost always" experienced playing at least half a game more often than other players; reported higher enjoyment, than those who played less regularly ( F = 35.6, P < .001). Importantly, players who reported higher levels of enjoyment also reported greater intentions to continue playing rugby ( F = 6.4, P < .002). Findings support the use of CE to facilitate player enjoyment in team sports and could lead to reduced attrition in youth sport more generally.